Comparison of Laws Regulation of Indonesian and Malaysian Sole Companies - Br Tarigan, Violeta Desfina (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
The establishment of a Sole Proprietorship, known as Perseroan Perorangan in Indonesia and Sendirian Berhad (Sdn Bhd) in Malaysia, aims to facilitate micro and small business enterprises (MSMEs) by allowing a single individual to establish a limited liability company. This paper compares the legal frameworks governing Sole Proprietorships in Indonesia and Malaysia, focusing on aspects such as legal definitions, establishment requirements, authorized capital, corporate liability, and dissolution procedures. The research employs a normative legal method, analyzing statutory regulations, legal doctrines, and academic sources. Findings indicate that while both countries recognize the single-member company concept, Indonesia enforces stricter eligibility criteria, allowing only Indonesian citizens to establish Perseroan Perorangan, whereas Malaysia permits both locals and foreign residents. Moreover, Malaysia's legal framework provides more flexibility regarding shareholder numbers and capital requirements. The study concludes that regulatory harmonization and further legal clarifications are necessary to enhance the effectiveness of Sole Proprietorship policies in both jurisdictions.